CHRONIC EATING DISORDERS IN YOUNG CHILDREN – OBESITY (PARATROPHIA): PATHOGENETIC MECHANISMS, RISK FACTORS, PREVENTION AND NUTRITION CORRECTION (LECTURE) - Миняйлова, Наталья Николаевна; Ровда, Юрий Иванович; Черных, Наталья Степановна (Mother and Baby in Kuzbass, 2021)
The article covers the issues of terminology, classification, etiology and diagnostic of excessive nutrition in young children. It presents the risk factors of overweight and obesity in accordance with the age. It also reflects the aspects of breastfeeding of newborns with macrosomia and young children with overweight.
Keywords: paratrophia; obesity; eating disorders; risk factors; children